2016
DOI: 10.1128/aac.01243-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characteristics of NDM-Producing Enterobacteriaceae Isolates in Australia and Their bla NDM Genetic Contexts

Abstract: e bla NDM has been reported in different Enterobacteriaceae species and on numerous plasmid replicon types (Inc). Plasmid replicon typing, in combination with genomic characteristics of the bacterial host (e.g., sequence typing), is used to infer the spread of antimicrobial resistance determinants between genetically unrelated bacterial hosts. The genetic context of bla NDM is heterogeneous. In this study, we genomically characterized 12 NDM-producing Enterobacteriaceae isolated in Australia between 2012 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 42 publications
(51 reference statements)
5
57
0
2
Order By: Relevance
“…However, we were unable to establish such a link. pKpN01-NDM7 is an IncX3 plasmid; IncX3 plasmids are usually self-transferable and have been associated with the spread of several antimicrobial-resistant genes, including carbapenemase genes, such as bla NDM (33)(34)(35)(36)(37), bla KPC (38), and bla OXA-181 (39,40). A BLAST search against the GenBank sequence database revealed that pKpN01-NDM7 is highly similar to other bla NDMharboring IncX3 plasmids, including pNDM-HN380 (bla NDM-1 ) (36), p112298-NDM (bla NDM-1 ; GenBank accession number KP987216), pEc1929 (bla NDM-5 ; GenBank accession number KT824791), pNDM_MGR194 (bla NDM-5 ) (34), pJEG027 (bla NDM-4 ) (35), and pOM26-1 (bla NDM-7 ; GenBank accession number KP776609) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we were unable to establish such a link. pKpN01-NDM7 is an IncX3 plasmid; IncX3 plasmids are usually self-transferable and have been associated with the spread of several antimicrobial-resistant genes, including carbapenemase genes, such as bla NDM (33)(34)(35)(36)(37), bla KPC (38), and bla OXA-181 (39,40). A BLAST search against the GenBank sequence database revealed that pKpN01-NDM7 is highly similar to other bla NDMharboring IncX3 plasmids, including pNDM-HN380 (bla NDM-1 ) (36), p112298-NDM (bla NDM-1 ; GenBank accession number KP987216), pEc1929 (bla NDM-5 ; GenBank accession number KT824791), pNDM_MGR194 (bla NDM-5 ) (34), pJEG027 (bla NDM-4 ) (35), and pOM26-1 (bla NDM-7 ; GenBank accession number KP776609) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The NDM-5-encoding gene bla was first identified in an Escherichia coli strain recovered from a patient in the United Kingdom in 2011 (3). Since then, bla was identified in many countries, such as Algeria (4)(5)(6), the United States (7), Australia (8), China (9)(10)(11)(12), Denmark (13), Japan (14), India (15), and the United Kingdom (3). The widespread occurrence of NDM-5 in recent years should arouse our attention.…”
mentioning
confidence: 99%
“…Limited studies have described the plasmid features and genetic contexts of NDM-producers from Australia (22,75,227).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Treatment options for these infections are diminishing with isolates frequently reported as resistant to major last-line antimicrobials, such as carbapenems and colistin (22,23). The genes conferring resistance to major classes of antimicrobials are often carried on extrachromosomal DNA elements, known as plasmids, which can act to disseminate these genes amongst the broader bacterial population (2,39,40,198).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation